Crafting lives : African American artisans in New Bern, North Carolina, 1770-1900 - Bishir, Catherine W. (The University of North Carolina Press, 2013)
From the colonial period onward, Black artisans in southern cities - thousands of free and enslaved carpenters, coopers, dressmakers, blacksmiths, saddlers, shoemakers, bricklayers, shipwrights, cabinetmakers, tailors, and others - played vital roles in their communities. Yet only a very few Black craftspeople have gained popular and scholarly attention. The author remedies this oversight by offering an in-depth portrayal of urban African American artisans in the small but important port city of New Bern. In so doing, she highlights the community's often unrecognized importance in the history of nineteenth-century black life. Drawing upon myriad sources, the author brings to life men and women who employed their trade skills, sense of purpose, and community relationships to work for liberty and self-sufficiency, to establish and protect their families, and to assume leadership in churches and associations and in New Bern's dynamic political life during and after the Civil War. Focusing on their words and actions, this book provides an understanding of urban southern black artisans' unique place in the larger picture of American artisan identity.--description provided by publisher.